The Study on The Influence of Differential Responsiveness of Judges in Participant Performances During Moot Court Presentations - B, LEELESH SUNDARAM; SUNDARAM, ASHA; V, VISHNU PRIYA; R, GAYATHRI. (The journal of contemporary issues in business and government, 2020)
Large law firms show affinity towards students who have participated in moot court. Because these understudies already spent many hours perfecting the analytical, research, and writing aptitudes that practicing attorneys must have. As a result moot court have gained high importance in the legal front but In the recent times presentation and arguments of students (mooters) in moot court competition vary from competition to competition, though academic pressures and preparation is put forth as a reason, it is apprehended that the responsiveness of judges may also be a reason for the same. Judges in moot courts occupy important role, the judges pave way for students to learn court manners and patience, in the moot court presentation. The recent behavior of students towards moot court presentation and participation gives way to apprehend that the judge’s responsiveness may be a reason for differential skillful and intellect presentation in competitions. Therefore this research aims at the influence of differential responsiveness of judges in the performance of participants. by the virtue of non probability convenience sampling and using chi square tests it could be found out that There is no relationship between student opinion on differential responsiveness of judges and year of study, There is no relationship between student opinion on Influence of judges responsiveness in participant presentation and year of study. The study put forth that the performance of students in moot court competitions is influenced by differential responsiveness of judges. Therefore the study recommends that only qualified experts of the subject matter must be preferred as judges in the moot court competitions.